2013
DOI: 10.3892/ol.2013.1403
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ROS/AMPK signaling pathway in tetramethylpyrazine-induced apoptosis in gastric cancer cells

Abstract: Tetramethylpyrazine (TMPZ) is one of the active compounds extracted from the traditional Chinese medicinal herb Chuanxiong and several studies have shown it to possess anticancer properties. However, its effectiveness in gastric cancer and its cellular mechanisms are relatively unknown. The present study aimed to investigate the effect of TMPZ on SGC7901 cells, and it was demonstrated that a high dose of TMPZ inhibited cell viability and induced apoptosis by stimulating AMP-activated protein kinase (AMPK) thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…The results revealed that 8e could induce FaDu cells' apoptosis in a dose-dependent manner. This was consistent with other reports showing TMP and its derivatives could induce apoptosis of cancer cells [22][23][24].…”
Section: Apoptosis Analysis By Annexin V-fitc/pi Stainingsupporting
confidence: 94%
“…The results revealed that 8e could induce FaDu cells' apoptosis in a dose-dependent manner. This was consistent with other reports showing TMP and its derivatives could induce apoptosis of cancer cells [22][23][24].…”
Section: Apoptosis Analysis By Annexin V-fitc/pi Stainingsupporting
confidence: 94%
“…The anti-cancer properties of TMP have been observed in many types of cancer. It was shown that TMP induced ROS generation and activated mitochondrial-mediated apoptotic pathway in human gastric cancer [20]. TMP may inhibit proliferation of lymphocytic leukemia and gastric carcinoma cells [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Tetramethylpyrazine (TMP) (2,3,5,6-tetramethylpyrazine; C 8 H 12 N 2 ) is one of the bioactive ingredients extracted from the rhizome of the Chinese herb Ligusticum. Studies have demonstrated that TMP has potent inhibitory effects on a variety of tumors through affecting the proliferation and migration of tumor cells (10)(11)(12). In our previous study, TMP was found to inhibit the growth of HL-60 cells by inducing their differentiation (13).…”
Section: Introductionmentioning
confidence: 88%